A Review Article on Current Pharmacological Status of Cardioprotective Plant - Sarita Yadav; Bindu singh yadav; Nandini Chaudhary; Rajneesh Kumar; Ravi Yadav; Shashwat Pandey (Current Research in Pharmaceutical Sciences, 2023)
Cardiovascular diseases involve abnormalities of the heart and blood vessels, such as coronary heart disease, hypertension, and cerebrovascular disease, and are the main cause of the increase in mortality rate in the world. Herbal plants tend to be very useful to prevent cardiovascular disease. The phytoconstituents of herbal medicinal plants like tannins, alkaloids, saponins, flavonoids, and glycosides that have the ability to prevent cardiovascular diseases. Examples such as Nerium oleander, Amaranthus viridis, Ginkgo biloba, Daucus carota, Gingerol, Tinospora cordifolia etc. Many studies investigated the cardioprotective effect of these natural products against experimentally-induced myocardial damage, and their results revealed that their potential phytochemicals exhibited significant antioxidant, anti-apoptotic, anti-inflammatory, anti-atherosclerotic activities. The review highlights the promising mechanisms and probable applications of various herbal plants, and their phytochemicals in the prevention and treatment of cardiovascular diseases. The cardioprotective plants contain a wide- variety of bioactive compound involve with diosgenin, isoflavones, sulforaphane, carotinized, catechin and quercetin are increasing the cardio protection and decreases the chances of cardiac abnormalities.